Role of dexmedetomidine in myocardial protection during beating coronary artery bypass grafting. - Alpesh Sarvaia; Jigisha Pujara; Varsha Sarvaiya; Himani Pandya; Visharad Trivedi; Sunil Kumar Ninama; Himanshu Acharya (International Journal of Medical Research and Review, 2017)
Background: On-pump CABG is associated with a high risk of myocardial injuries and other complications that result into myocardial ischemia and arrhythmias. OPCAB surgery may reduce, although not entirely eliminate, these myocardial injuries. This prospective study was designed to determine whether the intraoperative use of Dexmedetomidine could reduce the incidence of myocardial injuries after off pump CABG.Methods: A total of 100 patients who underwent off-pump coronary artery bypass surgery were included and randomly divided into Dexmedetomidine treated and Control groups (groups B and A, respectively) 50 patients in each groups. Following the first vascular anastomosis grafting, the patients in group B received a loading dose of 0.5 μg/kg/10min of Dexmedetomidine via central venous catheter followed by a continuous infusion of 0.5 μg/kg/hr of Dexmedetomidine. The infusion was discontinued at the end of surgery. In group A, 0.9% physiological saline was infused using identical methods to group B.Results: The primary outcomes measured included serum levels of cardiac biomarkers like CPK-MB & Trop I. Secondary outcomes included hemodynamic stability, ischemia or arrhythmia events & post-operative ICU stay. Dexmedetomidine use significantly reduced postoperative CPK-MB (26.38 ± 7.11 v/s 30.48 ± 9.84, P=0.019) & Trop I (0.678 ± 0.742 v/s 1.011 ± 0.67, P=0.021) at 24 & 48 hours respectively. Intraoperative dexmedetomidine therapy also reduced the risk of overall complications.Conclusion: Intra operative administration of low-dose dexmedetomidine reduces myocardial damage during off-pump coronary artery bypass grafting surgery as indicated by significantly decreased level of cardiac biochemical markers, CK-MB and cTnI post-operatively.